2019
DOI: 10.1002/cptc.201900111
|View full text |Cite
|
Sign up to set email alerts
|

One‐ and Two‐Photon‐Induced Photochemistry of Iron Pentacarbonyl [Fe(CO)5]: Insights from Coupled Cluster Response Theory

Abstract: We present herein the first comprehensive study of the oneand two-photon absorption of Fe(CO) 5 utilising a hierarchy of linear-and quadratic-response coupled cluster (LR-and QR-CC) methodologies to provide an in-depth characterisation, as well as potential energy curves for axial and equatorial bond dissociations, highlighting the state crossings leading from the bright 1A 2 '' state through to the dissociative 1E' state. We have characterised a range of metal-to-ligand charge transfer (MLCT) and ligand field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…The use of these methodologies for the accurate determination of TPA spectra has been well established across a range of molecules of both biological and photochemical importance. [47][48][49][50][51][52][53] The structures studied here are presented in three groups: the first involves small functional group alterations to the core pterin moiety at the C6 (Table 1); the second involves the inclusion of extended side chains (Fig. 2) centred around the folic acid structure (FA); the final grouping of structures (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The use of these methodologies for the accurate determination of TPA spectra has been well established across a range of molecules of both biological and photochemical importance. [47][48][49][50][51][52][53] The structures studied here are presented in three groups: the first involves small functional group alterations to the core pterin moiety at the C6 (Table 1); the second involves the inclusion of extended side chains (Fig. 2) centred around the folic acid structure (FA); the final grouping of structures (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…A recent reinvestigation of the λ = 266 nm photolysis of Fe(CO)5 using X-ray photoelectron spectroscopy confirms the loss of successive CO ligands yielding, first, Fe(CO)4 and then, on a longer timescale, Fe(CO)3 fragments, and suggested that these processes occur solely on singlet potential energy surfaces (PESs) 18 − the feasibility of which has since been validated by coupled cluster response theory calculations. 19 Gerber and co-workers also reported ultrafast pump-probe fragmentation studies of the halfsandwich metal complex of current interest, dicarbonylcyclopentadienyliodoiron(II) (η 5 -CpFe(CO)2I, henceforth CpFe(CO)2I), using λ = 400 nm pump pulses and detecting with a λ = 800 nm MPI probe pulse. 20 The time evolving parent and fragment ion yields were interpreted by assuming primary Fe-CO and Fe-I bond fission processes, with sequential loss of the remaining ligands leading to eventual detection of Fe + fragment ions.…”
Section: Introductionmentioning
confidence: 99%
“…An additional, lower‐intensity region of absorption is present between 2.5–3.9 eV (490‐320 nm), peaking at ≈3 eV (415 nm). Absorption in this region is expected to correspond to metal‐to‐ligand charge‐transfer (MLCT) transitions, with recent TDDFT calculations indicating that ligand‐to‐metal charge‐transfer (LMCT) transitions are present …”
Section: Resultsmentioning
confidence: 97%